Analysis of thermomechanical properties of polymeric materials produced by a 3D printing method - Gnatowski, Adam (Array, 2019)
A comparative analysis of the thermomechanical properties of semicrystalline and amorphous polymeric materials was carried out. Samples were produced by using a 3D printing technology on the SIGNAL printer - ATMAT. The following polymeric materials were used to make the samples: TPU-thermoplastic polyurethane elastomer, ABScopolymer acrylonitrile-butadiene-styrene, Nosewood, PET-ethylene terephthalate, PLA-poly (lactic acid). The research included a thermal analysis of the dynamic properties (DMTA) of manufactured materials.